State of the landed resources of pool river of gorin' - Клименко, М. О. (Scientific Progress & Innovations, 2012)
Aiming results of researches from the study of the agrarian ecological state of earths of the agricultural setting of river of Goryn' basin on the indexes of ecological stability, level of the anthropogenic loading and state of agrarian landscape. It is set that relatively the satisfactory state is characterize territories of districts which belong to the area of Polesya, and the most vulnerable and unstable are territories of districts of area of Forest-steppe.